Tinjauan Spasial Upah Menurut Jenis Kelamin dan Kaitannya Dengan Indeks Kesetaraan dan Keadilan Gender di Indonesia - Iskandar, Yusuf; Hamid, Abdul (Jurnal Bisnisman : Riset Bisnis dan Manajemen, 2019)
The purpose of this study is to review spatially the wages based on sex in Indonesia and review spatially the relationship between wages based on sex with the Gender Equality and Equity Index (IKKG) in Indonesia. The area, which is the location of this research, is the administrative region of the Republic of Indonesia, from now on referred to as Indonesia. The primary data used in this study are data on net wages and sex, as well as IKKG data from BAPPENAS. The data year used is 2010. This data will then be analyzed through 2 (two) stages, namely spatial analysis with the help of ArcGIS 10.0 and the relationship test using a cross table. Based on the calculation of the ratio presented through a spatial review, it can be seen that from 33 provinces in Indonesia, there are only two provinces whose wage ratio is below 100, that's mean, 31 provinces in Indonesia, the women, receive fewer wages than men. Nationally, based on the Indonesian KHL limits in 2010, the average female worker in Indonesia still received an inadequate salary, while male workers in Indonesia in 2013 received an average wage. In northern Sumatra and Eastern Indonesia, besides Papua has a reasonably low IKKG. Wage inequality based on sex can be a severe problem in the field of labor in Indonesia, and this inequality, if not solved immediately, will significantly hamper the role of women in poverty alleviation, because female workers will find it difficult to achieve financial independence and economic self-sufficiency.